К этимологии лат. līma ‘напильник’ - Филимонов, Евгений Геннадьевич (Philologia Classica, 2007)
The subjеct of the paper is etymology of Lat. līma ‘file’. The author establishes a semantic developmental parallel with Slavic, where we observe the sequence *tek- ’to flow’ > Russian ток ’current’ > точило ’file, sharpener’. In Latin we find: *lei- ’to pour’ > *loios > *loi-ō ’to cause to flow, to wipe, to rub’ > *loimā > līma ’file’. Non-diphthongal vs. diphthongal variants of the root ’lei-’ are encountered in other Indo-European languages, e. g. Old Indic layate ’sticks together’ and līyate ’lies beside’.